Delancey [large type] : a man, a woman, a restaurant, a marriage - Wizenberg, Molly (Thorndike Press, a part of Gale Cengage Learning, 2014)
When Molly Wizenberg married Brandon Pettit, he was a trained composer with a handful of offbeat interests: espresso machines, wooden boats, violin-building, and ice cream-making. So when Brandon decided to open a pizza restaurant, Molly was supportive--not because she wanted him to do it, but because the idea was so far-fetched that she didn't think he would. Before she knew it, he'd signed a lease on a space. The restaurant, Delancey, was going to be a reality, and all of Molly's assumptions about her marriage were about to change.